The Impact of Social Marginalization on Mental Health in Middle Eastern Conflict Zones - Nurzahara Sihombing; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar (Calory Journal Medical Laboratory Journal, 2025)
This systematic review aims to comprehensively evaluate the consequences of social marginalization on the mental health conditions of populations in Middle Eastern conflict zones, utilizing data from 2015 to 2024. Through a critical examination of 47 studies that met the inclusion criteria, a markedly high prevalence of mental disorders within this population was identified, namely post-traumatic stress disorder (PTSD) at 42.8% (95% CI = 38.4–47.2), major depression at 37.6% (95% CI = 33.2–42.0), and generalized anxiety disorder at 35.3% (95% CI = 31.1–39.5). Furthermore, the results of the meta-analysis revealed a very strong and statistically significant correlation between social marginalization and the severity of mental health disorders (r = 0.73, p < 0.001), indicating that the more intensely an individual experiences various forms of social marginalization, the more severe the psychological disorders they endure. Moreover, the three most dominant determinants of social marginalization were identified as limited access to healthcare services (OR = 3.82, 95% CI = 3.14–4.50), the persistence of systemic discrimination (OR = 3.45, 95% CI = 2.87–4.03), and widespread social isolation (OR = 3.21, 95% CI = 2.66–3.76). These findings not only expand upon the prior research outcomes of Al-Krenawi and Graham (2009) and Amsalem et al. (2025), which were confined to the aspect of PTSD but also provide new empirical evidence concerning a broader spectrum of mental disorders as well as specific patterns of social marginalization within the conflict landscape of the Middle East. Finally, this study contributes significantly to the academic literature by elaborating on the complex interactive mechanisms between practices of social marginalization and mental health deterioration while offering a framework for community-based interventions that are responsive and adaptive to the socio-political conditions characteristic of Middle Eastern conflict zones.